الإسهامات الدعوية للعمل الخيري الخاص في المملكة العربية السعودية - المصعبي، ناجي بن أحمد (جامعة الأزهر - كلية اللغة العربية بجرجا, 2018)
الحمد لله الذي بنعمته تتم الصالحات، وصلى الله وسلم على الهادي البشير، والسراج المنير، المبعوث رحمة للعالمين وعلى آله وصحابته أجمعين ومن اقتفى أثرهم إلى يوم الدين وبعد: فقد ظهر من خلال هذا البحث عدد من النتائج المهمة وهي كالتالي: مشروعية العمل الخيري في الكتاب والسنة. من أهم مؤسسات العمل الخيري الدعوي في المملكة العربية السعودية مؤسسة أوقاف الراجحي، ومؤسسة العنود الخيرية، ومؤسسة السبيعي الخيرية ومؤسسة أوقاف محمد الراجحي الخيرية. أهم مناشط مؤسسة أوقاف الراجحي الخيري في المجال الدعوي كان الإنفاق على طلبة العلوم الشرعية والدعاة، وطباعه الكتب، وإنشاء المدراس الإسلامية لتحفيظ القرآن الكريم. أهم مناشط مؤسسة العنود الخيرية في مجال الدعوة كرسي البحث العلمي، طباعة الكتب العلمية، إقامة الدورات العلمية، دعم مكاتب الجاليات، التكفل برحلات علمية لطلاب العلم. أهم مناشط مؤسسة محمد وعبد الله إبراهيم السبيعي الخيرية في مجال الدعوة نمذجة دار نسائية لتحفيظ القرآن ومكتب جاليات، تنفيذ الدليل الشامل لتأهيل الداعيات. من أهم مناشط مؤسسة محمد عبد العزيز الراجحي الخيرية في المجال الدعوي برنامج رعاية لكفالة ١٠٠ طالب علم، مشروع دليل المسلم الجديد، مشروع المعرف الإلكتروني بالإسلام ومشروع المكتبة المرئية باللغات العالمية.
Contributions to charitable work in the Kingdom of Saudi Arabia A number of important results emerged from this research: 1. The legitimacy of charitable work in the Qur'aan and Sunnah. 2. One of the most important philanthropic institutions in Saudi Arabia is Awqaf Al Rajhi Foundation, Al Anoud Charitable Foundation, Al-Subaie Charity Foundation and Awqaf Mohammed Al-Rajhi Charity Foundation. 3. The most important activities of the Al-Rajhi Charity Foundation in the field of advocacy was spending on students of Islamic sciences and preachers, printing books, and establishing Islamic schools to memorize the Holy Quran. 4. The most important activities of Anoud Charity Foundation in the field of advocacy scientific research chair, printing scientific books, the establishment of scientific courses, support of the offices of communities, scientific trips to science students. 5. The most important activities of the Mohammed and Abdullah Ibrahim Al-Subaie Charitable Foundation in the field of advocacy, modeling a women's house to memorize the Quran and the Office of Communities, implementing the comprehensive guide for the rehabilitation of the dai'at. 6. One of the most important activities of the Mohammed Abdul Aziz Al Rajhi Charitable Foundation in the field of advocacy is a sponsorship program to ensure 100 students of science, the new Muslim guidebook project, the electronic knowledge project in Islam and the visual library project in international languages.
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- الأعمال الخيرية الخاصة -- الجمعيات الخيرية -- الإسهامات الدعوية -- الدعوة الإسلامية -- السعودية -- المجتمع السعودي -- مستخلصات الأبحاث